(3GdEjVGM TQM GdeUHGMs - (3CMeO Hf jMji Hf CMeO Hf MGHS GdOhGQj GdUYOjs; (3CMeO Hf GdMSf Hf eMeO Hf eMeO Hf CHj HcQ GdQUGU,J (B621 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfTC GdYGde ef GdYOe , hGNJQYg ENJQGYkG hHYO adeG cGf Yde GdcdGe (B: (3CTQa GdYdhe Ch gh deYQaI GdMi Gdbjhe CMHHJ Cf CYdb TQMkG eajOkG Ydi GdcJGH GdeYQha HeUHGM GdYdhe s
(3BNQgG (B:s
(3hai eG PcQfGg caGjI def CfUa faSg , hde jYe GdJYUH Yjf HUjQJg , hef EgJOi adfaSg hfMf fSCd Gddg Cf jLYdfG HGdYde YGedjf , ceG LYdfG dg MGeOjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3aQZ GdeDda ef JCdjag hfSNI SfI (B1038 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJhMjO hGdedd hGdfMds